2008
DOI: 10.1103/physrevb.77.172501
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the mechanism that determines the critical current density in polycrystalline superconductors using time-dependent Ginzburg-Landau theory

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
3
26
0
1
Order By: Relevance
“…1,22 Access to variable-temperature and variable-strain measurements (in one probe) on a single sample enabled a resolution of the apparent contradiction between strain scaling (found at fixed temperature) 18 and temperature scaling (at fixed strain). [23][24][25][26] This led to a general scaling law 23,24,27 for LTS materials which includes a 1/κ 2 term 28 (κ: GinzburgLandau constant) that gives best fits to the data for Nb 3 Sn 23,29 and Nb 3 Al 30 and is consistent with computational data 31 and general analytic forms. 32,33 An excellent bending beam apparatus was also developed at the University of Twente for short samples of LTS wires.…”
Section: Introductionsupporting
confidence: 59%
“…1,22 Access to variable-temperature and variable-strain measurements (in one probe) on a single sample enabled a resolution of the apparent contradiction between strain scaling (found at fixed temperature) 18 and temperature scaling (at fixed strain). [23][24][25][26] This led to a general scaling law 23,24,27 for LTS materials which includes a 1/κ 2 term 28 (κ: GinzburgLandau constant) that gives best fits to the data for Nb 3 Sn 23,29 and Nb 3 Al 30 and is consistent with computational data 31 and general analytic forms. 32,33 An excellent bending beam apparatus was also developed at the University of Twente for short samples of LTS wires.…”
Section: Introductionsupporting
confidence: 59%
“…In polycrystalline low temperature superconductors (LTS), such large forces were often achieved by reducing the grain size. This increased the force necessary to drive fluxons along the grain boundaries, from one side of the sample to the other, by increasing the density of grain boundary triple points and the distortions of the fluxons required for them to move [2,3]. In high temperature superconductors (HTS), the pinning force has often been increased by adding inclusions that pin each fluxon [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although high-field solutions for SNS J-Js are available 16,18 (36) and (37) in (9) and (10) to solve for c 1 …”
Section: Zero-field J C -Nonlinear Equations (/0 Ab )mentioning
confidence: 99%
“…We have long known that although characterizing grain boundary pinning using just the size of the grains is useful for describing similar superconducting materials with different grain sizes 35 , it is very simplistic. Visualisation of solutions to the TDGL equations 14 for polycrystalline materials has shown that fluxons cross the superconductor by flowing along the grain boundaries 36 37,38 .…”
Section: Concluding Comments and Future Workmentioning
confidence: 99%